Retrospective Comparison of the Myopia Master and the Lenstar LS900 Axial Length Measurements in Children with Myopia - Sivakumar, Thibika; Palmowski-Wolfe, Anja (Klinische Monatsblätter für Augenheilkunde, 2023)
Background This study is a retrospective analysis to compare ocular biometry measurements of axial length in children with myopia using Myopia Master (OCULUS, Wetzlar, Germany) and Lenstar LS900 (HAAG-STREIT AG, Köniz, Switzerland).Patients and Methods Axial length measurements obtained with both instruments within a 3-week period were collected retrospectively. Measurements were visualized with a Bland-Altman plot. For statistical evaluation, a paired t-test was applied, and the Pearson correlation coefficient (r) was established.Results Sixty-one eyes from 31 myopic patients (59% male, 41% female) with a mean age of 11.34 ± 3.25 years (range: 6 – 18 years) were identified. Mean axial length was 24.7 mm (SD 1.29) with the Myopia Master and 24.69 mm (SD 1.30) with the Lenstar LS900 (Pearson correlation: r = 0.9991). The average difference of the axial length measurement between the two biometers was 0.00 064 mm ± 0.056 SD (p = 0.9293).Conclusion The axial length measured by Myopia Master and Lenstar LS900 did not differ significantly. Thus, previous values obtained with the Lenstar LS900 can be applied to assess myopia progression.
Keywords: Myopia Master; Lenstar LS900; axial length; axial length measurement; myopia; myopia in children